Improving Self-Efficacy and Behavior to Prevent Transmission in Pulmonary Tuberculosis Patients through Health Coaching Based on Social Cognitive Theory - Mordekai Rangkoratat, Melinda; Melda Suhita , Byba; Ana Anggraini, Novita (Journal of Applied Nursing and Health, 2024)
Background: Pulmonary tuberculosis is an infectious disease that can be prevented with appropriate measures. However, many patients show low self-efficacy, leading to a lack of motivation to follow treatment and implement preventive measures. The research aim was Analyzing the Effect of Health Coaching based on Social Cognitive Theory on Self-efficacy and Transmission Prevention Behavior in Pulmonary Tuberculosis Patients. Methods: This quantitative research method uses a quasi-experiment design with a pretest-posttest control group design approach. The population of all Pulmonary Tuberculosis patients in the Working Area of the Lingat Health Center, Selaru District, Tanimbar Islands Regency is 49 people. The sample size was 34 respondents. The sampling technique is purposive sampling. The study's independent variables are Health Coaching based on Social Cognitive Theory, and the dependent variables are Self-efficacy and Transmission Prevention Behavior. Results: The analysis using the Wilcoxon test obtained p=0.000 Self-efficacy and p=0.001 Transmission Prevention Behavior, which means that there is an Effect of Health Coaching based on Social Cognitive Theory on Self-efficacy and Transmission Prevention Behavior in Pulmonary Tuberculosis Patients Conclusion: Blood circulation becomes smooth because of pressure point massage which can stimulate endorphin neurotransmitters in the autonomic nerves so that the body relaxes. Pressure point massage intervention can be applied as an alternative therapy option in the management of hypertension which supports the treatment of hypertension so that blood pressure can be well controlled.